Cost-utility of Protocols of BFM-ALL and UK-ALL for Treatment of Children with Acute Lymphoblastic Leukemia in Iran - Hadi HAYATI; Abbas KEBRIAEEZADEH; Mohammad Ali EHSANI; Shekoufeh NIKFAR; Ali AKBARI SARI; Azim MEHRVAR; Elham SHAHGHOLI (Tehran University of Medical Sciences, 2018)
Background: There is a requirement to assess the effectiveness and resources used in two protocols United Kingdom (UK-ALL) and Berlin-Frankfurt-Munster (BFM-ALL) that are most commonly used to treatment of ALL patients by oncologists in Iran. Accordingly, we analyzed the cost of treatment and utility of children treated with two protocols in Iran. Methods: The entire medical direct costs of patients in "BFM ALL" protocol and "UK ALL" protocol in multi-centers calculated from Apr 2010 to Jun 2015. For calculating utility and Quality Adjusted Life Year (QALY) of the patients, we used standard questionnaire Health Utilities Index 3 (HUI3). The patients and their parents were interviewed. Data were analyzed using software SPSS18 and EXCEL. Results: The average direct medical cost for each patient for BFM-ALL was 15026 USD and UK-ALL was 8282 USD which showed a significant difference in the total cost of the treatment in the two protocols (P≤0.02). Finally, there was a significant difference in the utility score of the maintenance phase of these two methods (P≤0.003). Conclusion: UK-ALL is dominant and BFM protocol is dominated by both sides total costs and utility and QALY. Mainly, more hospital stay in "BFM ALL" protocol is the cause of raised costs in this protocol. Consequently, by considering different QALYs in the methods and low costs in "UK ALL" protocol, "UK ALL" protocol is more preferred.